BETWEEN REASONABLE AND PROBABLE CAUSE AND MALICE IN THE LAW OF MALICIOUS PROSECUTION: A COMMONWEALTH UPDATE - Chuks Okpaluba (Obiter, 2016)
Although the requirements of absence of a reasonable and probable cause and malice are two distinct elements in an action for malicious prosecution, they sometimes appear inseparable. An absence of reasonable and probable cause might, in instances, be a clear indication of malice on the part of the prosecution. However, while the absence of reasonable and probable cause is often deduced from the conduct of the prosecutor, judged from the objective standpoint of a reasonable prosecutor possessed of the same information, malice is inferred from the state of mind of the prosecutor as to whether he or she genuinely intended to bring the accused person to justice, or had operated from the angle of vengeance, improper purpose, targeted malice or for any unlawful purpose. Such inference can easily be drawn where the investigating officer and the prosecutor knowingly relied on fabricated information – Minister of Safety and Security v Tyokwana 2015 (1) SACR 597 (SCA). The burden of proof of both elements, though extensively canvassed by the Australian High Court in A v New South Wales (2007) 230 CLR 500 (HCA), has been taken a step further by the New South Wales Court of Appeal in State of NSW v Quirk [2012] NSWCA 216. The Supreme Court of Appeal of South Africa has maintained in Woji v Minister of Police 2014 (1) SACR 409 (SCA) that negligence or gross negligence, short of dolus eventualis, would not suffice in a claim for malicious prosecution. The defendant must have been aware of the wrongfulness of his or her conduct in initiating or continuing the prosecution, but nevertheless continued to act, reckless as to the consequences of his or her conduct.